2020
DOI: 10.1021/acs.jpcb.0c03761
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry and Rippling in Mixed Surfactant Bilayers from All-Atom and Coarse-Grained Simulations: Interdigitation and Per Chain Entropy

Abstract: Understanding lateral organizations of self-assembled bilayers is crucial to gain a control on functionally relevant topologies. We study self-assembled bilayers composed of a surfactant, behenyl trimethyl ammonium chloride (BTMAC), a cosurfactant, stearyl alcohol (SA), at a ratio of 2:1 in the presence of water at 283 K employing subsequent all-atom (AA) and coarse-grained (CG) molecular dynamics simulations. Differences in initial configurations lead to the formation of bilayers at ripple or square phases or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 86 publications
0
32
0
Order By: Relevance
“…Molecular simulations at various levels of FF descriptions, ranging from all-atom and united atom models at the finer scales to DPD and MARTINI models at higher levels of coarse graining, have been extensively used to study the rich variety of equilibrium phases observed in model phospholipid bilayer membranes 1,17,76 . In particular, the rippled phase, sensitive to initial configurations, annealing protocols, and finite-size effects, has been challenging to capture using MD simulations 20,25,34,41 . Although all-atom FFs have successfully captured the formation of the ripple phase (Table 1), the ability of the widely used MARTINI force-fields to stabilize this intermediate phase, which occurs below the main gel-to-liquid crystalline transition, has been a matter of some debate 34,47 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Molecular simulations at various levels of FF descriptions, ranging from all-atom and united atom models at the finer scales to DPD and MARTINI models at higher levels of coarse graining, have been extensively used to study the rich variety of equilibrium phases observed in model phospholipid bilayer membranes 1,17,76 . In particular, the rippled phase, sensitive to initial configurations, annealing protocols, and finite-size effects, has been challenging to capture using MD simulations 20,25,34,41 . Although all-atom FFs have successfully captured the formation of the ripple phase (Table 1), the ability of the widely used MARTINI force-fields to stabilize this intermediate phase, which occurs below the main gel-to-liquid crystalline transition, has been a matter of some debate 34,47 .…”
Section: Discussionmentioning
confidence: 99%
“…43 BTMAC+SA 2020 All-atom, coarse-grained CHARMM36, MARTINI -Ref. 25 Abbreviations: DPD -dissipative particle dynamics; DPPC -1,2-dipalmitoyl-sn-glycero-3-phosphocholine; DMPC -1,2-dimyristoyl-sn-glycero-3-phosphocholine; BTMAC -benzyltrimethylammonium chloride; SA -stearyl alcohol.…”
Section: Dppc 2019mentioning
confidence: 99%
See 3 more Smart Citations